International Students at Canadian Community Colleges: Emerging Trends - Legusov, Oleg; Jafar, Hayfa; Bégin-Caouette , Olivier (Journal of International Students, 2023)
This study uses Knight’s (2004) framework of internationalization in higher education to examine emerging trends involving international students at Canadian public community colleges. The findings show that the provinces’ socioeconomic and cultural differences and immigration policies have had a substantial effect on the number of international students on college campuses. The study identified seven important emerging trends within the sector. The findings suggest that an evolving approach to immigrant selection may be contributing to the reconfiguration of the colleges’ international student body, which has gone from predominantly Chinese to primarily Indian. Furthermore, the study explores new approaches used to increase the market share of international students, such as campuses exclusively for international students and partnerships with private career colleges. It also provides an analysis of the latest development, namely the shift to online instruction in response to the COVID-19 pandemic. The study highlights the importance of understanding these trends.